1996
DOI: 10.1007/bf01252404
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free fatty acids by capillary zone electrophoresis

Abstract: Abstract. Capillary zone electrophoresis was investigated for the separation of free fatty acids as an alternative to well established techniques such as GC or HPLC. The analysis was performed with indirect UV detection in a counterelectroosmotic flow mode using a diethylbarbiturate carrier electrolyte at a pH between 10 and 11 in a mixed aqueous-organic solvent. Separation of saturated and unsaturated fatty acids could be achieved after bromination of the double bonds. Problems with wall adsorption of fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…1) and m EOF,buf is the EOF mobility in the buffer containing no zwitterion. The magnitude of the EOF increase is consistent with the statements within the literature [25,30]. Also, a similar linear dependence between streaming potential and concentration of zwitterions was observed by Reichmuth and Kirby [33].…”
Section: Z1-methylsupporting
confidence: 86%
See 2 more Smart Citations
“…1) and m EOF,buf is the EOF mobility in the buffer containing no zwitterion. The magnitude of the EOF increase is consistent with the statements within the literature [25,30]. Also, a similar linear dependence between streaming potential and concentration of zwitterions was observed by Reichmuth and Kirby [33].…”
Section: Z1-methylsupporting
confidence: 86%
“…In the separation of metallochromic ligands, Macka et al [30] found that the addition of 400 mM Z1-methyl to the BGE resulted in an increase in EOF. Buchberger and Winna [25] observed an approximately 30% increase in EOF when 500 mM Z1-methyl was added to the carrier electrolyte.…”
Section: Z1-methylmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, for optimized indirect A detection of FFA, the chromophore should preferably bear a negative charge and have a high molar absorptivity for high sensitivity, while its effective mobility must be close to that of the analytes to reduce electromigration dispersion. Different chromogenic species, such as dihydroxybenzoate [44], benzoate [45], diethylbarbiturate [46], chromate, naphtalenesulfonate and p-anisate [47], have been tested. Among these compounds, p-anisate seems to give the most satisfactory baseline stability, peak symmetry and sensitivity [48].…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…The separations are usually conducted counter-electroosmotically, so the longest chain fatty acids elute first, and under indirect UV detection. The most commonly used electrolyte systems are often buffered, include chromophoric agents (p-anisate [15,16], diethylbarbiturate [17], adenosine monophosphate [18], dodecylbenzenesulfonate (SDBS) [19][20][21][22]) and might comprise a variety of additives, such as organic solvents (methanol [15,16], ethanol [23], ACN [20][21][22], 1-octanol [21,22], methylformamidedioxane [18]), surfactants (sodium dodecyl sulfate, SDS [23,24], polyoxyethylene 23 lauryl ether (Brij 35 ® ) [18][19][20][21][22]), microemulsion oils [25] and cyclodextrins [16,20,23,24]. In addition, other detection schemes have also been implemented, such as LIF [26,27] and MS [28] with proper electrolyte systems reflecting the detection requirements.…”
Section: Introductionmentioning
confidence: 99%